Inhibition of HIV Replication by Cyclic and Hairpin PNAs Targeting the HIV-1 TAR RNA Loop - Upert, Gregory; Di Giorgio, Audrey; Upadhyay, Alok; Manvar, Dinesh; Pandey, Nootan; Pandey, Virendra N.; Patino, Nadia (Journal of Nucleic Acids, 2012)
Human immunodeficiency virus-1 (HIV-1) replication and gene expression entails specific interaction of the viral protein Tat with its transactivation responsive element (TAR), to form a highly stable stem-bulge-loop structure. Previously, we described triphenylphosphonium (TPP) cation-based vectors that efficiently deliver nucleotide analogs (PNAs) into the cytoplasm of cells. In particular, we showed that the TPP conjugate of a linear 16-mer PNA targeting the apical stem-loop region of TAR impedes Tat-mediated transactivation of the HIV-1 LTR in vitro and also in cell culture systems. In this communication, we conjugated TPP to cyclic and hairpin PNAs targeting the loop region of HIV-1 TAR and evaluated their antiviral efficacy in a cell culture system. We found that TPP-cyclic PNAs containing only 8 residues, showed higher antiviral potency compared to hairpin PNAs of 12 or 16 residues. We further noted that the TPP-conjugates of the 8-mer cyclic PNA as well as the 16-mer linear PNA displayed similar antiviral efficacy. However, cyclic PNAs were shown to be highly specific to their target sequences. This communication emphasizes on the importance of small constrained cyclic PNAs over both linear and hairpin structures for targeting biologically relevant RNA hairpins.